O terceiro ano do ciclo de alfabetização no Ensino Fundamental de nove anos: o que dizem alunos e professores - Campos, Flávia Roberta Velasco [UNESP] (2015)
The central objective of this study is to characterize and to analyze the work developed in the third grade of elementary school of nine years, from the perspective of students and teachers and considering the official legislations for the literacy cycle. The main issues of the study were: How is shaping up the third year of elementary school, from the perspective of students and teachers, mainly to objectives view which be concluded at the end of the literacy cycle, in accordance to official legislations? How the thirdgrade teacher is organizing your work? How childrens and teachers receive and conceive in this period? Finally, the childrens are literate at the end of the third year literacy cycle? In the observations, it adopts as theoretical-methodological grounds the bioecological perspective of Urie Bronfrenbrenner human development (1996). This research constitutes a qualitative approach. Therefore, observations were performed with records in field journal, in order to capture and understand the reality investigated. Semi-structured interviews with children and teachers was made, in order to capture the conceptions and perceptions, and a text production applied to children was performed, in attend to check how students appropriated the read and write knowledge. 20 students and their respective teachers participated of this research, provided by two classes of third year literacy cycle, from a public school in Araraquara, São Paulo State, during August to December 2013. The results were organized into two dimensions: the first discusses about the context organization of the school and the third years, and the second knowledge the pedagogical organization of the work, revealing conceptions and practices experienced. The results indicate some meanings assigned by students at school; their perceptions about the work developed by the teachers, the activities carried out in the school environment, reporting their difficulties and skills ...